The Influence of Motivation, Work Discipline, Leadership and Information Technology on The Performance of Educators at The Yayasan Santa Lusia Virgini Bekasi - Mewarni Siregar; Nyoman Sawitri; Dewi Puspaningtyas Faeni (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The purpose of this study was to determine the effect of motivation, work discipline, leadership and information technology on the performance of educators at the Yayasan Santa Lusia Virgini Bekasi. This study uses quantitative methods using probability sampling techniques. This study uses Smart PLS 3.0 software and tests are carried out, namely data analysis methods (descriptive and verification), evaluation of the measurement model (outer model), namely validity and reliability tests, evaluation of the structural model (inner model), namely the coefficient of determination or R-Square (R2), predictive relevance (Q2), and Goodness Of Fit Model Test and hypothesis testing, namely t test and F test. The results of this study partially the motivation variable has a positive and significant effect on performance with a standard value at the P-values level which is <0.05 (0.021 <0.05). The work discipline variable has a positive and significant effect on performance with a standard value at the P-values level, namely <0.05 (0.002 <0.05). The leadership variable has a positive and and significant effect on performance with a standard value at the P-values level, namely <0.05 (0.003 <0.05). The information technology variable has a positive and significant effect on performance with a standard value at the P-values level, namely <0.05 (0.000 <0.05) Meanwhile, the results of simultaneous research from motivation, work discipline, leadership, information technology have a positive and significant effect on performance with an F-count value of 185.58> F-Table 2.42 and the coefficient of determination (R2) on R-Square obtained a value of 0.811.